2002
DOI: 10.1103/physreve.66.066408
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of plasma turbulence–shear-flow dynamics through a transcritical bifurcation

Abstract: The structural properties of an economical model for a confined plasma turbulence governor are investigated through bifurcation and stability analyses. A close relationship is demonstrated between the underlying bifurcation framework of the model and typical behavior associated with low-to high-confinement transitions such as shear flow stabilization of turbulence and oscillatory collective action. In particular, the analysis evinces two types of discontinuous transition that are qualitatively distinct. One in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…The simplest approach that captures the essential physics underlying the problem is lowdimensional dynamical modeling and analysis [13,14,15,16], which can provide a very economical tool to predict the transition. However, the tradeoff with such highly coarsegrained modeling is that it necessarily whites out information, and may therefore miss important physics and predict unphysical singular behavior [15].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest approach that captures the essential physics underlying the problem is lowdimensional dynamical modeling and analysis [13,14,15,16], which can provide a very economical tool to predict the transition. However, the tradeoff with such highly coarsegrained modeling is that it necessarily whites out information, and may therefore miss important physics and predict unphysical singular behavior [15].…”
Section: Introductionmentioning
confidence: 99%
“…͑1͒-͑3͒ was found in Ref. 3 to predict shear flow suppresion of turbulence, hysteretic, nonhysteretic, and oscillatory transitions, and saturation then decline of the shear flow with increasing power input. All of these behaviors have been observed repeatably in diverse fusion plasma experiments.…”
Section: Introductionmentioning
confidence: 93%
“…The extended modeling and analysis in this work are based on the following reduced dynamical model for confinement transitions from Ref. 3:…”
Section: Introductionmentioning
confidence: 99%
“…The creation of an edge transport barrier formed by a sheared zonal flow is closely related to the L-H transition 3 . Ordinary differential equation (ODE) models for the L-H transition are based on the predator-prey relationship between zonal flow and turbulent flow, and incorporate a potential energy related to the pressure profile as an additional state variable [4][5][6][7][8][9][10][11][12] . Miki et al 13 and Wu et al 14 have both suggested 1D partial differential equation (PDE) models for the L-H transition based on this predator-prey relationship.…”
Section: Introductionmentioning
confidence: 99%